Integrasi Green Waqf Melalui Platform Digital Crowdfunding dan Dampak Sosialnya Bagi Masyarakat - Mochammad Salman Alfarisi; Nurul Huda (Universitas Islam Lamongan, 2023)
This study aims at finding out the integration of green waqf through the crowdfunding digital platform and the social impacts provided for the community. This research applies library research method and qualitative analysis approach. The integration of green waqf through the crowdfunding digital platform and its relationship to embody the sustainable development between generations. Green waqf is one of instruments of Islamic law to deal with the problems of the ummah, one of which is environmental problems related to sustainable development and intergenerational justice. This research was conducted qualitatively using analytical descriptive design. The results show that green waqf is able to balance development and environmental sustainability that leads to sustainable environmental preservation and equality between generations, where future generations are still at the same level of utilization as the current generation, in terms of variety of choices and access to resources. natural. Green waqf is an environmental conservation innovation movement that begins with raising funds through a crowdfunding mechanism, which results in the purchase of critical land to be reforested. As the critical land gets verdant and has ecological value, it will be donated to the village community on the condition that the forest must be maintained and must not be damaged. Green waqf does not only answer the problem of natural damage, but also brings benefits from various aspects of ecology, energy sustainability, social, economic, and community welfare.